1996 Seimas elections and the development of Lithuania’s party system - Novagrockienė, Jūratė (Politologija, 1997)
This article investigates several aspects to which 1996 Seimas elections contribute. The author argues that these elections confirmed certain tendencies in the development of the party system as well as attached new features to it. Aspects that have led to both a short-run victory of the conservative and the Christian democratic parties, and a long-run perspective – emergence of a multiparty system, are being researched profoundly. First of them displays the following points: amendments to the Law of Seimas Elections, their influence on the electoral behaviour of the parties and the suffragettes. The second point is the indices that have articulated certain division of the electoral votes. In the opening part of the article, the author elucidates some premises that have conditioned certain pre-electoral behaviour of the parties: the most important is that the parties reviewed the laws that regulate their activity. The author discusses the way how the new editorships of the Law on the elections affected the shift of the entire political system and resulted in 1996 elections. We are informed that the manipulatory power of the electoral system has been finally realised. The author depicts some discrepancies of the editorships to the law and propounds their threat to the stability of the entire political system. Adherently we are introduced to a valid aspect which concerns modifications in the electoral behaviour (and, forwardly, the results of the elections). Fragmentation of the political parties is given as evidence which has affected these modifications. The author analyses the causes that stipulated the electoral behaviour, the tendencies elections proved to exist and preferences the parties witnessed. In conclusion, the author challenges those who are convinced of the electoral stability (Table 1 portrays the distribution of the votes). An important theoretical question arises as the author endeavours to answer the question: ’what party system emerges in Lithuania’. We are shown the criteria which motivate and postulate the fact of the existence of the party system itself. By the same token, the author introduces three inductive indices which help to identify this existence, develops them and forces under empirical analysis. Qualitative and quantitative methods of the research are applied as the author tries to estimate quantitative shifts in the party system. These shifts are pictured in a number of graphs. Novagrockienė views positive consequences these 1996 Seimas elections have so far had, emphasises what concrete tendencies it has confirmed or revealed. This study is really rich in its content and is worth attentive analysis by the reader himself.